2021
DOI: 10.4037/ajcc2021423
|View full text |Cite
|
Sign up to set email alerts
|

Examining Burnout in Interprofessional Intensive Care Unit Clinicians Using Qualitative Analysis

Abstract: Background Health care professionals working in intensive care units report a high degree of burnout, but this topic has not been extensively studied from an interdisciplinary perspective. Objective To characterize experiences of burnout among members of interprofessional intensive care unit teams and identify possible contributing factors. Methods This quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Research has shown that patient mistreatment is unfortunately a significant factor for Black, indigenous, and people of color (BIPOC) and/or White people partnered with BIPOC individuals. 9 Additionally, clinician burnout has been well documented in research studies 16 ; however, these 2 phenomena are not discussed as they should be. Patient mistreatment and clinician burnout are 2 sides of the same coin because the structures in which we attempt to provide care need reimagination.…”
Section: Patient Mistreatment and Clinician Burnoutmentioning
confidence: 99%
“…Research has shown that patient mistreatment is unfortunately a significant factor for Black, indigenous, and people of color (BIPOC) and/or White people partnered with BIPOC individuals. 9 Additionally, clinician burnout has been well documented in research studies 16 ; however, these 2 phenomena are not discussed as they should be. Patient mistreatment and clinician burnout are 2 sides of the same coin because the structures in which we attempt to provide care need reimagination.…”
Section: Patient Mistreatment and Clinician Burnoutmentioning
confidence: 99%
“…Colbenson and colleagues describe the definition of burnout by the World Health Organization as a syndrome that develops when chronic stress isn't successfully managed 8. Nurses in the Cardiothoracic ICU were describing sentiments in which their core values and integrity were being dishonored, causing feelings of moral distress 9.…”
mentioning
confidence: 99%